Perlindungan Konsumen dalam Transaksi E-Commerce Ditinjau dari Undang-Undang Perlindungan Konsumen - Alfis Setyawan; Bella Wijaya (Fakultas Hukum, Universitas Internasional Batam, 2017)
E-commerce transaction is a trade or buy-and-sell, which are done through the internet media. E-commerce transaction used substantially by the society because of how prompt and efficient it is without having to directly meeting the seller. Ecommerce transaction is done through website or Online Retailer Provider. During the development, e-commerce transaction has several problems regarding the consumer’s protection, for example when the product sent by the Online Retailer Provider is not compatible or when there is a defective on the product received by the consumer. Those incidents harm the consumers. Thus, there is a necessity to conduct a research to figure the consumer’s protection in e-commerce transaction based on Law Number 8 Year 1999 on Consumer’s Protection (hereinafter referred as LOCP), this study further objective is to answer the question on the online retailer provider liability in e-commerce transaction based upon LOCP, how does the law protect the consumers in e-commerce transaction based upon LOCP and how to conduct the legal effort and the resolution of consumer’s dispute in e-commerce transaction based upon LOCP. This study is a juridical normative legal research. The data used are primary data, which consist of legislations and secondary data retrieved from library research. In this study the author used the method of data analysis by implementing qualitative approach. This approach is used towards the data retrieved from document studies and library materials. The law protections for consumer in e-commerce transaction based upon LOCP are divided into 3 (three) parts, which are before the transaction, during the transaction and after the transaction. Online Retailer Provider as a seller or the business-maker has a liability such as regulated in LOCP. The liability regulated in LOCP is the liability to use the presumption principle to always be regarded responsible and being in the state of absolute liability. Whereas the legal effort which could be undergone by the consumer in LOCP is not sufficient enough for the dispute resolution in e-commerce transaction due to the character of e-commerce transaction that does not need a direct meeting and the broadness of the territory in online transaction. Thus an alternative solution is needed to efficiently resolve the dispute such as Online Dispute Resolution.